Far-Field Sub-Wavelength Imaging of Two-Dimensional Extended Target Aided By Compact Planar Resonant Structures - Qiang Gao; Xiao-Hua Wang; Bing-Zhong Wang (IEEE Photonics Journal, 2018)
Two kinds of compact planar electrical resonant structures (PERSs) are proposed as the solution to realize far-field sub-wavelength imaging of extended target. The proposed structures have their advantages in low profile, compact size, and electrical coupling property. The conversion between evanescent and propagation waves of the two structures enables the sub-wavelength information to be carried to far-field. The first PERS consists of periodically distributed spiral resonators. With the help of background Green's function, sub-wavelength images of two-dimensional extended target with the resolutions of λ/11 from simulation and λ/7 from experiment are reconstructed in the far-field by multiple signal classification imaging method. The second PERS similarly consists of spiral resonators, which operate at different frequencies. Image of an extended target with a resolution of λ/17 from experiment is reconstructed from the spectra received in the far-field, without the use of the background Green's function. Both simulations and experiments are performed to validate the proposed structures. The sub-wavelength imaging results show that the proposed PERSs can be widely applied in new super-resolution imaging systems.